Glicerina bruta e uréia de liberação lenta na alimentação de bovinos de corte - Castañeda Serrano, Román David (2011)
This study was conducted to evaluate the effects of crude glycerin (CG) and slowly release urea (SRU, OptigenRII) in cattle diets on nutrient digestibility, rumen microbial protein synthesis, and rumen fermentation and kinetic in steers. The experimental design was a Latin square, and experimental periods lasted 21 days. In the first experiment, five Nelore steers (522±43 kg) were used, and treatments were: 0, 3, 6, 9 e 12% of CG based on the total dry matter diet. Dry matter intake (DMI), ruminal apparent digestibility (RDC), intestinal apparent digestibility (IDC), and total apparent digestibility coefficient (TDC) of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and non-fiber carbohydrates (NFC) were not affected (P>0.05) by treatments. However, fecal flow of ether extract (EE) was lower (P<0.05) and the IDC and TDC of EE was higher (P<0.05) as the level of CG increased. The inclusion of different levels of CG showed no difference (P>0.05) in microbial protein synthesis and ruminal kinetics. The min pH, average pH, max NH3-N and average NH3-N decreased linearly (P<0.05) as the level of CG in the diet increased. According to results obtained in this study, CG may be used in cattle diets up to 12% on diet dry matter in replacement of corn without affecting the studied parameters. In the second experiment four Nelore steers (565±45 kg) were used, and treatments consisted in replacement of urea by SRU (OptigenRII ), as following: 0 SRU= 100% urea; 33SRU= 66% urea e 33% OptigenRII; 66SRU= 33% urea e 66% OptigenRII and 100SRU= 100% OptigenRII. The DMI, RDC, IDC and TDC of DM, CP and NFC were not affected (P>0.05) by treatments. Rumen outflow of DM, OM and CP decreased and RDC of NDF increased (P<0.05) as the level of OptigenRII in the diet increased. The replacement of urea by OptigenRII showed no difference (P>0.05) in the microbial protein synthesis, rumen fermentation and rumen kinetics. According to information obtained in this study the use of SRU in the diet of beef cattle, only improved rumen NDF digestibility.